Effect of Zr, Nb and Ti addition on injection molded 316L stainless steel for bio-applications: Mechanical, electrochemical and biocompatibility properties - GÜLSOY, HAMİT ÖZKAN; GÜLSOY, NAGİHAN; MUTLU, ÖZAL; PAZARLIOĞLU, SÜLEYMAN SERDAR (ELSEVIER SCIENCE BV, 2015)
The research investigated the effect of Zr, Nb and Ti additions on mechanical, electrochemical properties and biocompatibility of injection molded 316L stainless steel. Addition of elemental powder is promoted to get high performance of sintered 316L stainless steels. The amount of additive powder plays a role in determining the sintered microstructure and all properties. In this study, 316L stainless steel powders used with the elemental Zr, Nb and Ti powders. A feedstock containing 62.5 wt% powders loading was molded at different injection molded temperature. The binders were completely removed from molded components by solvent and thermal debinding at different temperatures. The debinded samples were sintered at 1350 degrees C for 60 min. Mechanical, electrochemical property and biocompatibility of the sintered samples were performed mechanical, electrochemical, SBF immersion tests and cell culture experiments. Results of study showed that sintered 316L and 316L with additives samples exhibited high corrosion properties and biocompatibility in a physiological environment. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Powder injection molding; Sintering; Corrosion resistance; Biocompatibility; CORROSION; POWDER; GAS